Developing a Small-Scale Experimental Method for Evaluating the Effectiveness of Soil Improvement Using Prefabricated Vertical Drains - Misriani, Merley; Hakam, Abdul; Joleha, Joleha; Elianora, Elianora; Pebrilista Putri, Eka; Hasian, Dodi Kifrah (Journal of the Civil Engineering Forum, 2025)
Soft soils pose significant challenges in infrastructure development due to their low bearing capacity and high compressibility, which cause settlement and deformation over time through consolidation. Despite advancements in soil improvement techniques, faster and more efficient methods for accelerating soil consolidation remain crucial for achieving structural stability in a reasonable timeframe. Prefabricated Vertical Drains (PVD) have been widely adopted to accelerate soil consolidation, with their effectiveness typically evaluated through field-scale studies. However, field experiments can be time-consuming, costly, and influenced by site-specific variables, making controlled assessments challenging. We developed a small-scale laboratory experiment to evaluate the effect of PVD on soil consolidation. Soil samples were collected from the Padang-Pekanbaru Toll Road construction site in West Sumatra, Indonesia. Under controlled laboratory settings, two models were constructed—one with PVD and one without—using PVC pipes (20.32 cm diameter, 3.0 m height) filled with saturated soil to simulate field-scale soil columns. We found that PVD significantly enhanced soil consolidation. The rate of settlement on conditions without PVD was 1.2 times slower than that with PVD, particularly under lower loads. In contrast, PVD-enhanced models exhibit 5.3 times faster and greater settlement than conditions without PVD, along with 7.15 times higher water discharge. Metrics such as the coefficient of consolidation (Cv) and t90 values reinforced that PVD accelerated the consolidation process, particularly when subjected to higher loads. This study ultimately supports the development of more reliable laboratory methods for evaluating PVD applications, thereby enhancing design decisions across various consolidation scenarios and providing valuable insights for future infrastructure projects.